The roof technologies at low cost houses and the effect on thermal performance : materials - Zulhatta bin, Marzoki (University Malaysia Sarawak, UNIMAS., 2004)
This project is a preliminary research on thermal performances and roof technologies of low cost houses in Kuching. The research mainly emphasized on the materials used in the roof construction. The aim of the project is to investigate the thermal performance characteristics in the low cost houses whether they are providing comfortable condition or not to occupants.